Evaluasi Kinerja Operasional UMKM Jasa Kecantikan Berbasis Key Performance Indicators (KPI): Studi Kasus pada Mutiara Salon Yogyakarta - Tamara Dwi Rahayu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Background: Micro, small, and medium enterprises (MSMEs) in the service sector, especially beauty salons, have an important role in supporting the local economy. However, many MSME actors have not adopted a structured performance evaluation system. This research was conducted to fill the research gap related to the application of Key Performance Indicators (KPI) in measuring the operational performance of MSMEs in the service sector. Objective: This study aims to evaluate the effectiveness and efficiency of the operational performance of Mutiara Salon Yogyakarta through the application of nine key KPI indicators, as well as identify areas of strength and opportunities for managerial improvement. Methods: The approach of this research is qualitative descriptive with a case study method. Data was collected through in-depth interviews, direct observations, and in-salon documentation. Data analysis was carried out descriptively through the stages of data reduction, presentation, and conclusion drawn, with validity tested through triangulation of sources and methods. Results: The results showed that out of the nine KPI indicators, five indicators reached the maximum target (100%), three indicators were close to the target (75–84%), and one indicator reached 83% of the target. The overall total achievement was 91.32%, which reflects operational performance in the excellent category. Conclusion: The implementation of KPIs has been proven to be able to provide an objective picture of the performance of service MSMEs such as Mutiara Salon. These findings suggest that indicator-based evaluation systems can be used for more targeted strategic decision-making, strengthening internal efficiency, and increasing competitiveness in the service market.